+0  
 
0
186
1
avatar

3 cot^2(x) − 1 = 0

Guest Jun 1, 2017
 #1
avatar+87301 
+1

 

3 cot^2(x) − 1 = 0       add 1 to both sides

 

3 cot^2 (x)   =  1       divide both sides by 3

 

cot^2( x)  =   1/3       take the square root of both sides

 

cot (x)  =  ±√ (1/3)   = 

 

So

 

cot (x)  = √ (1/3)      and this happens at  pi/ 3   +  pi* n    where n is an integer

 

And

 

cot (x)  =  - √1/3)    and this   happens  at     -pi/3  +  pi*n   where n is an integer

 

 

 

cool cool cool

CPhill  Jun 1, 2017

12 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.